2022
DOI: 10.1186/s12871-022-01933-w
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital mortality and SpO2 incritical care patients with cerebral injury: data from the MIMIC‑IV Database

Abstract: Background Evidence regarding the relationship between in-hospital mortality and SpO2 was low oxygen saturations are often thought to be harmful, new research in patients with brain damage has found that high oxygen saturation actually enhances mortality. However, there is currently no clear study to point out the appropriate range for oxygen saturation in patients with craniocerebral diseases.  Methods By screening all patients in the MIMIC IV dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…Upon covariate adjustments, individuals with low SpO 2 exhibited a 0.4-fold higher risk of death compared to those with normal levels. This was basically consistent with previous similar research results ( 13 ). In delineating the intricate relationship between low SpO 2 levels and heightened mortality risk in our study cohort, the underlying mechanisms, while not fully elucidated, prompted compelling considerations.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Upon covariate adjustments, individuals with low SpO 2 exhibited a 0.4-fold higher risk of death compared to those with normal levels. This was basically consistent with previous similar research results ( 13 ). In delineating the intricate relationship between low SpO 2 levels and heightened mortality risk in our study cohort, the underlying mechanisms, while not fully elucidated, prompted compelling considerations.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, the risk of death in patients with notably high SpO 2 levels was 1.06 times higher than in those maintaining normal SpO 2 levels. These results harmonized with earlier research ( 13 ). However, the intricate relationship between high SpO 2 and heightened mortality in elderly T2DM patients with cerebral infarction remained enigmatic, but several plausible mechanisms have been proposed.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Another study reported that oxygen saturation is inversely related to the risk of death, where an increase in oxygen saturation reduces the risk of death [ 27 ]. One percent (1%) increase in oxygen saturation has resulted in an 8% decrease in the risk of death [ 28 ].…”
Section: Discussionmentioning
confidence: 99%